Local mechanical and frictional properties of Ag/MoS2-doped self-lubricating Ni-based laser claddings and resulting high temperature vacuum performance. (15th January 2020) - Torres, Hector; Rojacz, Harald; Čoga, Lucija; Kalin, Mitjan; Rodríguez Ripoll, Manel
Abstract: The present study investigates the local mechanical and frictional properties of Ag/MoS2 -based self-lubricating claddings in order to unveil the contribution to friction reduction of the different phase constituents present in the cladding. The cladding microstructure is formed by nickel dendrites surrounded by borides and homogeneously scattered pure silver pockets encapsulated within molybdenum and chromium sulfides that arise from the thermal decomposition of MoS2 during deposition. Particular attention is devoted to the latter, since their local mechanical and frictional properties are completely unknown. The nanotribological results show that chromium sulfides have a high hardness and a low intrinsic friction. This implies a twofold role in friction reduction. They provide intrinsic low friction and support friction reduction by silver smearing thanks to their high hardness. The presented microstructure is able to effectively control and reduce friction down to a value of 0.25 in vacuum at room temperature and 300 °C by the smearing of silver over the chromium sulfides. This friction reduction mechanism is enhanced by thermal softening of the pure silver phase at elevated temperatures, contrary to air atmosphere, where smearing is hampered by silver oxidation. This overall tribological performance makes the presented claddings potential candidates for space applications. Graphical abstract: Image 1 Highlights: Nickel-based self-lubricating cladding provide low friction in vacuum up to 300 °C. Nanotribological characterisation shows a high nanohardness and low intrinsic friction for chromium sulfide phases. Low friction attributed to silver smearing over hard chromium sulfides. Friction reduction does not come at the expense of a higher wear in the cladding. Adhesion to the counterbody is lowered about 20 fold at 300 °C.